Association between cardiovascular mortality and deprivation in the adult population of Russia - A. A. Zelenina; S. A. Shalnova; G. A. Muromtseva; A. V. Kapustina; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; N. S. Karamnova; O. B. Shvabskaya; S. A. Maksimov (Кардиоваскулярная терапия и профилактика, 2024)
According to the Federal State Statistics Service of Russia, from 1970 to 2019, cardiovascular diseases remain one of the main causes of death in Russia. To date, the relationship between cardiovascular mortality and deprivation in Russia remains insufficiently studied.Aim. To identify the relationship between regional deprivation and cardiovascular mortality among the adult population of Russia.Material and methods. The Russian deprivation index was used to measure the deprivation level. The index indicators were obtained from official Rosstat statistics and the All-Russian Population Census for 2010. Cardiovascular mortality by age (five-year groups) and sex in the constituent entities of Russia from 2006 to 2012 was obtained from the Russian database on fertility and mortality of the Center for Demographic Research of the Russian Economic School.Results. The fully adjusted model showed a reduction in mortality (Mortality Rate Ratio (MRR), 0,93; 95% confidence interval: 0,91-0,94) in regions with the greatest overall deprivation compared to the least deprived regions. There is a decrease in mortality in the most socially deprived regions compared to the least deprived ones. The fully adjusted model showed a trend toward increased mortality across levels of economic deprivation (from less deprived (Q2) to more deprived (Q3 and Q4) compared to least deprived regions (Q1)). Our study showed an increase in mortality in the most environmentally deprived regions — MRR, 1,02; 95% confidence interval: 1,00-1,04.Conclusion. The study established a link between general, social, economic and environmental deprivation and cardiovascular mortality.